The revealed comparative advantages of late-Victorian Britain - Brian D. Varian (European Historical Economics Society (EHES), 2016)
This paper calculates indicators of revealed comparative advantage (RCA) and revealed symmetric comparative advantage (RSCA) for 17 British manufacturing industries for the years 1880, 1890, and 1900. The resulting indicators show that the late-Victorian 'workshop of the world' was at a marked comparative disadvantage in a number of manufacturing industries. The paper then proceeds to identify the factor determinants of Britain's manufacturing comparative advantages (disadvantages) using a four-factor Heckscher-Ohlin model that relies upon these indicators. In contrast with previous scholarship, the manufacturing comparative advantages of late-Victorian Britain were in the relatively labour non-intensive industries, and this pattern became more pronounced throughout the period. The paper concludes with the observation that the factor determinants of Britain's manufacturing comparative advantages appear closer to those of the United States than had traditionally been thought.
Keywords: F11; F14; N63; N73; 330; comparative advantage; Heckscher-Ohlin; manufacturing; Britain; nineteenth century